2008
DOI: 10.1242/jcs.017145
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of EPHA2 receptor destabilizes adherens junctions via a RhoA-dependent mechanism

Abstract: EPHA2 receptor tyrosine kinase is overexpressed in several human cancer types and promotes malignancy. However, the mechanisms by which EPHA2 promotes tumor progression are not completely understood. Here we report that overexpression of a wild-type EPHA2, but not a signaling-defective cytoplasmic truncation mutant (ΔC), in human mammary epithelial cells weakens E-cadherin-mediated cell-cell adhesion. Interestingly, the total level of cadherins and the composition of the adherens junction complexes were not af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
103
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(109 citation statements)
references
References 45 publications
6
103
0
Order By: Relevance
“…oxidant-induced activation of Src and EGFR leading to hyper-phosphorylation of AJ proteins (E-cadherin, catenins, cortactin, and afadin), junctional disruption, and cell de-adhesion. A previous study also showed that overexpression of ephrin type A2 receptor (also identified herein) can destabilize AJs via a Src-and RhoA-dependent mechanism (33). Thus, hyper-activation of receptor tyrosine kinases other than EGFR may also promote loss of adhesion.…”
Section: Discussionsupporting
confidence: 66%
“…oxidant-induced activation of Src and EGFR leading to hyper-phosphorylation of AJ proteins (E-cadherin, catenins, cortactin, and afadin), junctional disruption, and cell de-adhesion. A previous study also showed that overexpression of ephrin type A2 receptor (also identified herein) can destabilize AJs via a Src-and RhoA-dependent mechanism (33). Thus, hyper-activation of receptor tyrosine kinases other than EGFR may also promote loss of adhesion.…”
Section: Discussionsupporting
confidence: 66%
“…48,70 Similarly, EphA2 overexpression was capable of disrupting adherens junctions through a RhoA-mediated mechanism in breast epithelial cells but, in this case, without altering adherens junction protein or phosphorylation levels. 74 Since 48 This migratory phenotype also depended on a serine 897 residue present on the EphA2 cytoplasmic tail, a site directly phosphorylated by Akt in the absence of ephrin binding. 76,77 EphA2 and Akt signaling may also intersect in normal mammary epithelial development since loss of Akt1 and Akt2 in mice disrupted expansion of the epithelial mammary tree during pregnancy and lactation similar to EphA2 loss.…”
Section: Eph Receptor and Ephrin Signaling In Breast Cancermentioning
confidence: 96%
“…7,9,42,43 A recent study has shown that overexpression of EphA2 destabilizes adherens junctions via a RhoA-dependent mechanism. 44 EphA2 has been also shown to promote tumorigenesis by enhancing angiogenesis. The effects on angiogenesis may be direct (EphA2 overexpression has been noted in angiogenic blood vessels and may contribute to vasculogenic mimicry) 18 or indirect (role in VEGF mediated angiogenesis).…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%